2016
DOI: 10.3382/ps/pew030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prebiotics, probiotics, and their combination on growth performance, small intestine morphology, and resident Lactobacillus of male broilers

Abstract: Effects of commercial antimicrobials and the individual and combinational use of commercial prebiotics and probiotics in feed from d zero to 41 on the growth performance, small intestine size, jejunal morphology, and ileal resident bacteria population of broiler chickens were determined. A total of 1,040 one-day-old male Ross × Ross 708 broilers were randomly distributed to 80 floor pens (5 treatments, 16 replications per treatment, 13 chicks per pen). Five dietary treatments were employed: 1) a corn soybean-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 42 publications
2
52
0
5
Order By: Relevance
“…In addition, several researchers 113,114 investigated the effects of naturally synthesised AMPs on chicken and they reported that the birds fed naturally synthesised AMPs had improved growth performance, gut morphology, mucosal immune characteristics and serum IgA levels compared to unsupplemented birds. In conclusion, AMPs have several beneficial effects on growth performance, nutrient digestibility, intestinal morphology and gut microbiota in animals 37,105 . Therefore, AMPs may be used as a viable alternative to AGPs in the poultry industry, if available on the market.…”
Section: Antimicrobial Peptides and Fermented Proteinmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, several researchers 113,114 investigated the effects of naturally synthesised AMPs on chicken and they reported that the birds fed naturally synthesised AMPs had improved growth performance, gut morphology, mucosal immune characteristics and serum IgA levels compared to unsupplemented birds. In conclusion, AMPs have several beneficial effects on growth performance, nutrient digestibility, intestinal morphology and gut microbiota in animals 37,105 . Therefore, AMPs may be used as a viable alternative to AGPs in the poultry industry, if available on the market.…”
Section: Antimicrobial Peptides and Fermented Proteinmentioning
confidence: 93%
“…Refs 31,36,37,41,[144][145][146][147] Prebiotics Stimulates the growth of non-pathogenic bacteria; provides substrates for the bacterial fermentation in the lower gut of the host; stimulates immunity and neutralises toxins; inhibits colonisation of pathogenic bacteria; provides energy and other limiting nutrients for intestinal mucosa; enhances growth and feed efficiency.…”
Section: Mode Of Action Impact On Animal Health Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most common species of probiotics belong in the families of Lactobacillus, Bifidobacterium and Streptococcus [9] with the first two families being mostly used in studies related to human health [10]. As these microorganisms are naturally found in the gut microbiota, most studies are focused on their effects in the context of the natural function in the gut and as preventive or therapeutic agents against disease development [11][12][13][14][15][16][17][18]. To this end, probiotics have been used for the study and treatment of intestinal diseases such as gastroenteritis [19], intestinal hyperpermeability [20], urinary tract infection [21], intestinal dysbiosis [22], irritable bowel syndrome [23], Crohn's disease [24], colon cancer [25,26], ulcerative colitis [27,28] and peptic ulcer [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, this continuous use of antibiotics resulted in development of drug-resistant bacteria, drug residues in the body of animals, and imbalance of normal microflora. Different natural substances, such as probiotics, prebiotics (Wang et al, 2016), phytobiotics (Abd El-Hakim et al, 2009;Hassan et al, 2015), enzymes (Ao et al, 2009;Benţea et al, 2010), humic substances (Šamudovská & Demeterová, 2010), and acidifiers (Byrd et al, 2001;Eftekhari et al, 2015), can be used as feed additives and may improve health of animals, reduce microbial pathogens (e.g. Escherichia coli, Salmonella or Campylobacter) without the use of antibiotics, and enhance nutrition digestibility for better performance and to decrease the accumulation of ammonia in premises.…”
Section: Introductionmentioning
confidence: 99%